Effects of Diets with Graded Levels of Canola Meal on the Growth Performance, Meat Qualities, Relative Organ Weights, and Blood Characteristics of Broiler Chickens - An,BK (2016)
ABSTRACT This experiment was conducted to evaluate the dietary supplementation of canola meal (CM) on the growth performance, carcass characteristics, antibody titers against Newcastle disease virus and Infectious bronchitis virus, and blood profiles of broiler chickens. In total 600 day-old feather-sexed Ross male broiler chicks were randomly assigned into five treatments with six replicates of 20 birds each for 35 days. Treatments consisted of five experimental diets containing 0 (control), 3, 5, 10, or 15% canola meal (CM). Final body weight (BW) was not affected by the dietary treatments. Daily BW gain (DWG) and feed intake linearly decreased as dietary CM inclusion increased during the starter phase (p<0.0001), but not during the grower and total rearing periods. Chicks fed the diet with 15% CM presented the lowest DWG during the starter phase. Breast meat yield of CM-fed chicks linearly decreased as CM inclusion level increased (p=0.0014). Dietary CM supplementation did not influence organ relative weights, except for the spleen, meat quality, or blood profile. The results suggest that the CM may replace soybean meal (SBM) with no detrimental effects on overall growth performance or physiological responses of broiler chickens. However, it is recommended that supplementing excess amount of CM into broilers' diet should be taken into account in practical diet formulation as it could impair growth performance at early age and lower breast meat yields.